Anticancer potential of bovine lactoferrin in colorectal and other cancers - a brief overview - Joanna Słoka; Barbara Strzałka-Mrozik (Polish Pharmaceutical Society, 2023)
Colorectal cancer (CRC) is the second leading cause of cancer-related death in the world, thus constitutes a serious medical challenge. Due to the high mortality and also large number of recurrences of the disease, great emphasis is placed on the screening of people from high risk groups as well as the use of chemopreventive agents in chronic inflammation of the intestine. Chemoprevention is an early intervention decreasing risk of cancer development. Term chemoprevention comes from 1976 and is explained as "use of a synthetic or natural substance to decrease the risk of cancer developing, delay the time of cancer onset, or to reverse the carcinogenesis process." Lactoferrin (Lf) is a glycoprotein, which is included as a member of the transferrin family. It is able to reversibly bind iron ions, thus participating in maintaining iron homeostasis in the body. Lf mainly appears in the milk of most mammals, but also occurs in different biological fluids like tears, saliva, mucus and bronchial secretions. Lactoferrin is a multipotent molecule which exerts animicrobial, antiviral, antiparasitic and antifungal activity. Moreover, Lf has anti-inflammatory, immune regulatory and anticancer properties. Lf increases the immune system ability to eliminate cancer cells, thus preventing cancer development. Lf treatment was also found efficient in inhibiting proliferation, migration, survival and induction programming cell death in cancer cells. The present paper aims to review the molecular basis of lactoferrin chemopreventive effect in colorectal cancer. Bovine lactoferrin (bLf) acts both on stimulating immunological anticancer response and also directly through inducing cell cycle arrest, apoptosis or inhibition cell migrations. Moreover Lf boosts the effect of chemotherapy and alleviates its side effects. Finally, Lf is a nutraceutical characterized by high selectivity toward cancer cells and simultaneously has a high safety profile. It has considerable potential in the fight against CRC in both prevention and treatment.